Refeudalización Desigualdad social, economía y cultura política en América Latina en el temprano siglo XXI - Kaltmeier , Olaf (Afrontar las crisis desde América Latina, 2019)
In contemporary societies we see a state of social inequality as in the old regime: the accumulation of wealth in 1% of the population, multimillionaires as presidents, the increase in luxury consumption, the emergence of a culture of distinction, as well as the concentration of the earth and the spatial segregation. To understand these phenomena in a coherent interpretative framework, this essay proposes the hypothesis that in the early 21st century we are experiencing a new combination of refeudalization at the global level, but with specific regional features. In Latin America, this concept is particularly useful for understanding the return of the right to power after a period of leftist governments.